2008
DOI: 10.1007/s11695-007-9295-8
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the “NAFLD Fibrosis Score” in Morbidly Obese Subjects with NAFLD

Abstract: The NAFLD fibrosis score may be a useful noninvasive approach for excluding significant and advanced fibrosis and in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 14 publications
(15 reference statements)
1
32
0
Order By: Relevance
“…Of these, the NAFLD fibrosis score is the most widely known nowadays. [24][25][26][27] This study showed that T2DM was significantly associated with the presence of NAFLD in a morbidly obese population.…”
Section: Discussionmentioning
confidence: 59%
“…Of these, the NAFLD fibrosis score is the most widely known nowadays. [24][25][26][27] This study showed that T2DM was significantly associated with the presence of NAFLD in a morbidly obese population.…”
Section: Discussionmentioning
confidence: 59%
“…The NAFLD fibrosis score (NFS) has proven useful in accurately predicting as well as excluding advanced hepatic fibrosis using high and low cut-off values, respectively. Although the NFS has been extensively investigated and validated in different population groups, it has limited utility in intermediate stages of non-severe fibrosis [110][111][112] . The BARD score compares favourably to the NFS, and is both easier to calculate and does not produce intermediary results of indeterminate significance.…”
Section: Cardio-metabolic Risk Traits and Liver Enzyme Levelsmentioning
confidence: 99%
“…Algorithms specifically derived from NAFLD cohorts include the BAAT score (consisting of BMI, ALT, age and TG levels) [225], the BARD score (BMI, AST/ALT ratio, diabetes) [202,226] and the NAFLD fibrosis score (incorporating age, glucose, AST, ALT, BMI, platelets and albumin) [201,222,223,227,228]. In a recent meta-analysis the AUROC for the NAFLD fibrosis score was found to be 0.85 with a pooled sensitivity of 90 % and specificity of 97 % [143].…”
Section: Noninvasive Markers Of Fibrosis In Nafldmentioning
confidence: 99%